Comparative Effectiveness of Remestemcel-L-rknd versus Ruxolitinib in Pediatric Patients with Steroid-Refractory Acute Graft-Versus-Host Disease using Simulated Treatment Comparisons - Gabriel Tremblay; Dimitrios Tomaras; Eric Strati; Anna Forsythe (Journal of Health Economics and Outcomes Research)
**Background:** Allogeneic hematopoietic stem cell transplantation (allo-HSCT) can be a lifesaving treatment for hematologic malignancies, but acute graft-versus-host-disease (aGVHD) is a potentially deadly adverse effect experienced by up to half of allo-HSCT recipients. Inadequate response to steroid therapy for aGVHD is associated with poor prognosis and high mortality, including among pediatric patients, who are the focus of this study. Ruxolitinib and remestemcel-L-rknd were evaluated for the treatment of steroid-refractory (SR) aGVHD in two separate single-arm trials. To effectively compare the safety and efficacy of these treatments without a head-to-head trial, a simulated treatment comparison (STC) was conducted.